Bahasa Inggris - Ayu Mandasari; Retno Triwoelandari; Noor Isna Alfaien (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
This study aims to determine the critical thinking skills of grade 5 students in science lessons before and after the implementation of project-based learning, describe the implementation of project-based science learning in grade 5, and identify the inhibiting and supporting factors in the learning process. The research method used is mixed methods with sequential explanatory design, which is the collection and analysis of quantitative data followed by qualitative data to strengthen the research results. The sample in this study amounted to 60 students divided into a control class of 30 students, and an experimental class of 30 students. The results showed that the average pretest score of the experimental class was 73.70, while the control class was 58.07. After treatment, namely the application of project-based learning in the experimental class, the average value of the experimental class posttest increased significantly to 84.10, while the average value of the control class posttest which was not given special treatment, increased to 67.83. The results showed that the application of project-based science learning had an influence in improving students' critical thinking skills. In addition, the results showed that the inhibiting factors of project-based learning are time constraints, limited resources, such as teaching materials, equipment and facilities, limited teacher knowledge and skills, and student resistance. While the supporting factors are the availability of resources, such as teaching materials, equipment, and facilities, teacher involvement, and collaboration between teachers and students.